Proficient Replication of the Yeast Genome by a Viral DNA Polymerase - Stodola, Joseph L. (J Biol Chem, 2016)
DNA replication in eukaryotic cells requires minimally three B-family DNA polymerases: Pol α, Pol δ, and Pol ϵ. Pol δ replicates and matures Okazaki fragments on the lagging strand of the replication fork. Saccharomyces cerevisiae Pol δ is a three-subunit enzyme (Pol3-Pol31-Pol32). A small C-terminal domain of the catalytic subunit Pol3 carries both iron-sulfur cluster and zinc-binding motifs, which mediate interactions with Pol31, and processive replication with the replication clamp proliferating cell nuclear antigen (PCNA), respectively. We show that the entire N-terminal domain of Pol3, containing polymerase and proofreading activities, could be effectively replaced by those from bacteriophage RB69, and could carry out chromosomal DNA replication in yeast with remarkable high fidelity, provided that adaptive mutations in the replication clamp PCNA were introduced. This result is consistent with the model that all essential interactions for DNA replication in yeast are mediated through the small C-terminal domain of Pol3. The chimeric polymerase carries out processive replication with PCNA in vitro; however, in yeast, it requires an increased involvement of the mutagenic translesion DNA polymerase ζ during DNA replication.